1965
DOI: 10.1039/jr9650000843
|View full text |Cite
|
Sign up to set email alerts
|

154. The tautomerism of arene and ditertiary phosphine complexes of ruthenium(0), and the preparation of new types of hydrido-complexes of ruthenium(II)

Abstract: Chatt and Davidson 843 154. The Tautornerism of Arene and Ditertiary Phosphine Complexes of Ruthenium(O), and the Preparation of New Types of Hydrido- complexes of Ruthenium(rr) .* By J. CHATT and J. M. DAVIDSON.The reduction of truns-[RuCl,(PP) ,] (PP = Me,PCH,CH,-PMe,) by " arene " negative ions (arene = benzene, naphthalene, anthracene, and phenanthrene) has given a new series of hydrido (aryl) -complexes typified by cis-[RuH(2-Cl0H,) (PP),] (Ia). Members have been characterised from their physical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
1
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 242 publications
(113 citation statements)
references
References 0 publications
1
107
1
4
Order By: Relevance
“…When these rhodium and iridium precursors were complexed with chelating bisphosphines (e.g., dmpe or depe), they reacted readily with NCAs and gave living polymerizations. 15 Successful controlled polymerizations were also found with the isoelectronic zerovalent iron and ruthenium complexes, (PMe 3 ) 4 Fe 22 and (dmpe) 2 Ru, 23 which also readily undergo two-electron oxidative-addition reactions. Preliminary studies on these complexes indicated that all metals react initially at the anhydride bond of the NCAs and not at the NOH position.…”
mentioning
confidence: 90%
“…When these rhodium and iridium precursors were complexed with chelating bisphosphines (e.g., dmpe or depe), they reacted readily with NCAs and gave living polymerizations. 15 Successful controlled polymerizations were also found with the isoelectronic zerovalent iron and ruthenium complexes, (PMe 3 ) 4 Fe 22 and (dmpe) 2 Ru, 23 which also readily undergo two-electron oxidative-addition reactions. Preliminary studies on these complexes indicated that all metals react initially at the anhydride bond of the NCAs and not at the NOH position.…”
mentioning
confidence: 90%
“…Concomitant with Shilov's original work on electrophilic systems, observations from other laboratories seemed to point in an entirely opposite direction as the most promising route to C-H activation (8,42,43). Led by Chart's 1965 discovery of the reactions of the extremely electron-rich species Ru(dmpe) 2 (eq 5), several other examples were discovered in which apparently electron-rich metal centers were found capable of oxidatively adding C-H bonds.…”
Section: Oxidative Addition Of C-h Bonds: Early Examplesmentioning
confidence: 99%
“…However in 1983, Eisenberg discovered that Rh(PPh 3 ) 2 (CO)Cl photochemically catalyzed the carbonylation of benzene (94)(95)(96). As this reaction was assumed to proceed via photoextrusion of a ligand (either CO or PPh 3 ) the importance of three-coordinate d 8 fragments with respect to carbonylation was highlighted early. Accordingly, in fast timescale studies by Ford, C-H activation by Rh(PR 3 ) 2 Cl was observed directly (97).…”
Section: Insertion Of Co and Isonitriles Into C-h Bondsmentioning
confidence: 99%
See 2 more Smart Citations